Study of Metric Space and Its Variants - Surjeet Singh Chauhan (Gonder); Prachi Garg; Kamleshwar Thakur (Journal of Mathematics)
The objective of this paper is to present a comparative study of metric space and its variants. This study will provide the structure, gap analysis, and application of metric space and its variants from 1906 to 2021.